The Role Of The Cooperative Economics Subject To Develop The Character And Interest In Cooperative Student Of The Economics Education Major, Faculty Of Economics And Businesss, Makassar State University - Tuti Supatminingsih (Cita konsultindo, 2023)
This article is a study of Cooperative Economics which aims to examine more deeply regarding the role of cooperative economics in fostering or cultivating the character and interest in cooperatives for students of the Economics Education Study Program, Faculty of Economics and Business, Makassar State University. The results of this study discuss the role of cooperatives in cooperative economics courses for students of the Economics Education Study Program, Faculty of Business Economics, Makassar State University, where through this cooperative economics course it is hoped that they will be able to foster character and interest in cooperatives, especially those at Makassar State University. So that cooperatives at Makassar State University can provide a role and place for the community's economy.